Information quality and the valuation of new issues - Titman, Sheridan; Trueman, Brett (Journal of Accounting and Economics, 1986)
The prevailing belief in the marketplace holds that the choices of auditor and investment banker affect the price of an initial public offering. This belief reflects the idea that the auditor and investment banker quality provides information about the firm's true value. This paper presents a model giving this belief theoretical support. Under plausible conditions, it is shown that an entrepreneur with favorable information about his firm's value chooses a higher-quality auditor and investment banker than an entrepreneur with less favorable information. As a result, firm value is an increasing function of auditor and investment banker quality.